Effects of Feeding Time Restriction During the Whole Rearing Period on the Growth Performance of Broiler Chickens - Azis , A.; Berliana, S.; Afriani, (International Journal of Poultry Science, 2018)
Background and Objective: Feeding time restriction is an alternative lower-intensity feed restriction practice and could be less stressful than higher-intensity feed restriction practices. Feeding time restriction is more likely to provide the beneficial effects of feed restriction without adverse effects on growth. This study aimed to determine the effects of feeding time restriction on the growth performance of broiler chickens during the 35 days production period. Materials and Methods: Three hundred 1-day-old unsexed broiler chickens of the Lohmann commercial strain were used in a completely randomized design with 4 treatments and 5 replications. The treatments were as follows: broilers were fed ad libitum as a control group (P-0); broilers had free access to feed for 8 h day–1 from 1-21 days of age and then were fed ad libitum from 22-35 days of age (P-1); broilers had free access to feed for 8 h day–1 from 1-21 days of age and then for 12 h day–1 from 22-35 days of age (P-2); broilers had free access to feed for 12 h day–1 from 1-21 days of age and then were fed ad libitum from 22-35 days of age (P-3); and broilers had free access to feed for 12 h day–1 from 1-35 days of age (P-4). Body weight and feed intake values were recorded weekly and body weight gains and feed conversion ratios were calculated. Two broiler chickens from each pen were used to measure the size of the carcass, abdominal fat pad and internal organs at 35 days of age. Results: At 21 day of age, the body weight and body weight gain values of the broilers that had feeding time restrictions (P-1, P-2, P-3 and P-4) were significantly lower than those of the broilers fed ad libitum (P-0). No significant effects of the feeding time restriction treatments on body weight gains were found during the growing period from 22-35 days of age but at 35 day of age, the P-3 broilers had no significant differences in body weight compared to the weight of the broilers fed ad libitum (P-0). At 21 day of age, feed intake values and feed conversion ratios in the feeding time restriction treatments were significantly lower than those in P-0. However, the P-2 and P-4 broilers had lower feed intake values and feed conversion ratios during the growing period at 35 day of age. There were no differences among the treatments in the weights of the carcass, abdominal fat pad and gizzard; however, the weights of the internal organs, such as the liver, small intestine and pancreas, were significantly increased in broilers that experienced smaller feeding time restrictions. Conclusion: Program for restricting feed for 12 h day–1 from 1-21 days of age could be applied as a useful rearing management technique, resulting in a lower feed intake and no detrimental effects on the performance of broiler chickens.